Exogenous Reactive Oxygen Species Augments SMAD4 Expression And TGF-β Paradox in Human Breast Cancer - Roy, Avany Vinod; Padmanabhan, Renjini Ambika; Ramachandran, Rajesh (http://dharmais.co.id/, 2024)
Background: The Transforming growth factor-β (TGF-β) functions to induce apoptosis, cell cycle arrest, and differentiation is central to sustaining tissue homeostasis and maintaining genomic stability. TGF-β normally, an effective tumor-suppressor that restricts the uncontrolled division of cells augments the development and progression of human malignancies when cytostatic activities of TGF-β are resisted by genetic and epigenetic events caused by tumorigenesis. This dichotomic nature of TGF-β during oncogenesis termed as “TGF-β Paradox,” persists to be the most crucial and puzzling query regarding its physio-pathological function and the role of cellular antioxidant status is highly interrelated which warrants more studies on the role of endogenous reactive oxygen species (ROS) in deciding epithelial-mesenchymal transition (EMT) process. The objective of the study was to check whether enhanced ROS augments the TGF-β pathway facilitating EMT. Methods: In vitro toxicity assay was performed to assess the appropriate concentration of hydrogen peroxide (H2O2) imparting oxidative stress. Comet assay and 8-OHdG (8-hydroxy-2’-deoxyguanosine) enzyme-linked immunosorbent assay (ELISA) were performed to check the extent of DNA damage and adduct production respectively. Mitogen-activated protein kinase (MAPK) p38 ELISA and mRNA gene expression analysis of TGF-β and SMAD were done to verify the effect of H2O2 on these signaling. Results: The objective of the study was to check whether enhanced ROS augments the TGF-β pathway facilitating EMT. Along with morphological alterations, a dose-dependent decrease in cell viability was seen at 300µM of H2O2 compared to 75µM. DCFDA labeling discovered the dose-dependent gradation of intracellular ROS generation and this was correlated to increased cellular DNA damage and DNA adduct production which was increased linearly with increasing H2O2 as evident with comet test and 8-OHdG ELISA. Significantly reduced MAPK p38 activity revealed by indirect ELISA analysis suggests lessened suppression of cell growth. Conclusions: The study establishes that higher intracellular ROS will facilitate the TGF-β paradox leading to epithelial mesenchymal transition which can adversely affect therapeutic strategies targeting EMT